Structural Behavior of Reinforced Self-Compacted Engineered Cementitious Composite Beams - Mohammed, B.S. (Hindawi Limited, 2016)
Eight large-scale reinforced self-compacted engineered cementitious composite (R-SC-ECC) beams with different steel reinforcement ratios have been designed, prepared, cast, cured, and tested to failure at the age of 28 days. The experimental results have been compared with theoretical values predicted using EC2, RILEM, and VecTor2 models. Results show that failure modes in flexure and shear of R-SC-ECC beams are comparable to that of normal reinforced concrete beam. Nevertheless, contrary to VecTor2, models of EC2 and RILEM are not suitable for predicting reasonable ultimate moments for the beams, while results using VecTor2 model have successfully predicted the failure modes and load-deflection curves for all R-SC-ECC beams. It has been concluded that R-SC-ECC fall in the category of ductility class medium to high which gives advantages of using R-SC-ECC beams in regions susceptible to seismic activities. Â© 2016 Bashar S. Mohammed et al.